Subcutaneous fat necrosis of the newborn: clinical manifestations in two cases - Milena Pires de Campos Luciano Gomes; Adriana Maria Porro; Milvia Maria Simões da Silva Enokihara; Marcos César Floriano (Sociedade Brasileira de Dermatologia, 2013)
Subcutaneous fat necrosis of the newborn is an unusual form of panniculitis, with few cases described in medical literature. The disease affects newborns at term or post-term, with normal general health. We describe two cases of newborns affected by the disease. One of them already had lesions since birth. Also, we discuss the use of puncture for diagnostic assistance.